The analysis of theses subjects for relevance determination of research areas - Бережний, Микола Миколайович; Чубенко, Вікторія Анатоліївна; Хіноцька, Алла Анатоліївна; Мацишин, Сергій Олегович; Шепель, Ганна Олександрівна (Technology audit and production reserves, 2014)
The analysis of subjects of theses on the specialty 05.16.05 - "Metal forming" in Russia for the period 2000-2011 and theses on the specialty 05.03.05 - "Processes and machines of metal forming" in Ukraine for the period 2000-2012 was conducted in the paper. Considering PhD theses on technical disciplines as the highest level of scientific development in specific professional areas, it was decided to investigate retrospectively the subject array of all scientific works, defended in Russia for the period 2000-2011 and in Ukraine for the period 2000-2012. 236 theses on the named specialty were defended in Russia, 92% of which by males and 8% by females. In the field of non-ferrous 45 (19%) metals, the theses of metal forming of aluminum alloys prevail, next come copper alloys and other. 191 (81%) PhD theses are devoted to ferrous metal forming. Longitudinal rolling of strips and sheets is the most studied. 155 abstracts for the period 2000-2012 were considered during the study of theses in Ukraine. Systematization of theses, defended in Russia and Ukraine for the 2000-2012, expressed in graphs was conducted. Several theses, devoted to the rheological properties of matter and ultra-fine grain materials obtaining in metal forming were also noted.